Characterization of Japanese color sticks by energy dispersive X-ray fluorescence, X-ray diffraction and Fourier transform infrared analysis - Manso, M. (2012)
This work comprises the use of energy dispersive X-ray fluorescence (EDXRF), X-ray diffraction (XRD) and Fourier transformed infrared (FTIR) techniques for the study of the composition of twentieth century traditional Japanese color sticks. By using the combination of analytical techniques it was possible to obtain information on inorganic and organic pigments, binders and fillers present in the sticks. The colorant materials identified in the sticks were zinc and titanium white, chrome yellow, yellow and red ochre, vermillion, alizarin,indigo, Prussian and synthetic ultramarine blue. The results also showed that calcite and barite were used as inorganic mineral fillers while Arabic gum was the medium used. EDXRF offered great potential for such investigations since it allowed the identification of the elements present in the sample preserving its integrity. However, this information alone was not enough to clearly identify some of the materials in study and therefore it was necessary to use XRD and FTIR techniques.